Future direction of language education in Malaysia. - Osman, Hajibah; Pandian, Ambigapathy; Mat Daud, Nuraihan; Mohd. Don, Zuraidah; Salleh, Che Ibrahim; Harun, Minah; Mohd Yusof, Noraini; Rethinasamy, Soubakeavathi; Ma'alip, Halimah; Rafik-Galea, Shameem; Mohd. Din, Che Fatimah Dinna; Leon, Carol Elizabeth; et al. (Penerbitan Universiti Kebangsaan Malaysia: Kuala Lumpur, 2010)
language labs, and language specialists. This report is presented into three parts. The first part describes the evolution of language instruction in tertiary institutions (Chapter 1-2). The second part offers more analytical details on the range of approaches and practices that are observable in these institutions as well as the employment opportunities for the graduates (Chapter 3-5). In the third part, capsule summary of the findings and the implications are discussed (Chapter 6-7).